Influence of Germinated Brown Rice Production by Water Spraying Method on Its Qualities - Thatchapol Chungcharoen; Sansanee Sansiribhanb; Ronnachart Munsin; Ratiya Thuwapanichayanan; Arkom Palamanit; Phanphruek Sukkeaw; Kittisak Phetpan (Current Applied Science and Technology, 2022)
This study was aimed to compare the production time (germination and drying process) and quality of germinated brown rice (GBR) obtained from the water spraying-based GBR production (Sprayed-GBR) system and the water soaking-based GBR production (Soaked-GBR) system. The results showed that the Sprayed-GBR, in the germination process, required 2.5 h for spraying in a water spraying step to obtain paddy with the moisture content of 30% (w.b.) and 26 h in an incubation step to obtain the 90% germination percentage. This led to a shorter germination time compared to the Soaked-GBR, which required a germination time of 50 h for a 90% germination percentage. After germination, the moisture content of the Sprayed-GBR was lower than that of the Soaked-GBR. This provided a shorter drying time in the Sprayed-GBR (27 min) drying process compared with the Soaked-GBR (33 min). For GBR qualities, the Sprayed-GBR could decrease the unpleasant odor problem by providing a smaller number of attached microorganisms after germination (Shade drying), leading to a significantly higher score in the odor and the overall acceptability than the Soaked-GBR. This indicated that the Sprayed-GBR got more consumer acceptance. Moreover, the head rice yield value of the Sprayed-GBR was not different from that of the Soaked-GBR. However, the Sprayed-GBR provided a significantly lower GABA content and a significantly higher percentage of fissured kernels than the Soaked-GBR.
Keywords: GABA and Rice Research; Rice Cultivation and Yield Improvement